South Korea and Taiwan: Lessons of experience - Alcázar, Lorena (1990)
​This article reviews the various positions in the debates that the economic success of South Korea and Taiwan have raised. Peru and other developing countries are looking for the right lessons. In particular, they want to know whether the implementation of an export oriented strategy alone was decisive for the Korean and Taiwanese success. If not, which other elements were decisive? The paper aims to show that an export oriented strategy represents only one of the necessary elements to economic success and that, in the cases of South Korea and Taiwan, government intervention was significant, and characterized by pragmatism, efficiency, and flexibility. Furthermore, commitment to development, and a free economic environment for exporters appear to be crucial elements.​